2022
DOI: 10.1093/jme/tjac148
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Pyrethroid Resistance: Combinations of Cymbopogon nardus and Ocimum americanum Essential Oils Improve the Bioefficiency Control Against the Adults’ Populations of Aedes aegypti (Diptera: Culicidae)

Abstract: Dengue vector control strategies are mostly based on chemicals use against Aedes aegypti populations. The current study aimed at investigating the insecticidal effects of essential oils (EOs) obtained from five plant species, Cymbopogon citrates (D. C.) Stapf. (Poaceae), Cymbopogon nardus (Linn.) Rendle (Poaceae), Eucalyptus camaldulensis Linn. (Myrtaceae), Lippia multiflora Moldenke (Verbenaceae), and Ocimum americanum Linn. Lamiaceae, and combinations of Cymbopogon nardus and Ocimum americanum on Ae. aegypti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…gambiae (Balboné et al 2022b(Balboné et al , 2022c. In addition to their toxic effect shown recently by Balboné et al (2022bBalboné et al ( , 2022c, L. multi ora exerted an irritant effect on Anopheles and Aedes populations. That is useful in terms of its use in vector control strategies.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…gambiae (Balboné et al 2022b(Balboné et al , 2022c. In addition to their toxic effect shown recently by Balboné et al (2022bBalboné et al ( , 2022c, L. multi ora exerted an irritant effect on Anopheles and Aedes populations. That is useful in terms of its use in vector control strategies.…”
Section: Discussionmentioning
confidence: 80%
“…aegypti and An. gambiae, respectively (Balboné et al 2022b(Balboné et al , 2022c. On the other hand, studies conducted in Guinea Bissau, West Africa, had reported that O. americanum EO had also a repellent effect on Anopheles mosquitoes (Pålsson & Jaenson, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations